A study on electric pulse treatment of stainless steel constructive forming process. Issue 1 (1st December 2022) - Deng, J D; Han, T; Li, W T; Wang, F; Qian, D S
Abstract : The constructive forming process is a new plastic forming process of manufacturing heavy forgings from small blank units. In this process, first, the surfaces of the blank units are cleaned, and then the blank units are packaged into a whole blank, finally, the whole blank is deformed into a heavy forging by thermal deformation in a vacuum. In order to solve the key problem of constructive forming which is bonding interface healing, electric pulse treatment was introduced to regulate and control bonding interface healing. Through the electric pulse treatment experiments of stainless steel blanks before and after high temperature deformation, the effects of electric pulse treatment on the geometric morphology, microstructure and chemical composition of stainless steel bonding interface were revealed. The results indicate that using electrical pulse treatment before high temperature deformation can pre-connect the bonding interface and promote the thermal deformation healing of the bonding interface, using electrical pulse treatment after high temperature deformation can promote the healing of micro-voids in the bonding interface area and further improve the healing effect of the bonding interface. The research results provide a new idea for solving the problem of interfacial traceless bonding technology in metal constructive forming.